Participatory visual methods: exploring young people's identities, hopes and feelings. Issue 2 (3rd April 2019) - Barley, Ruth; Russell, Lisa
ABSTRACT: Using visual ethnography as a participatory method that places children's and young people's everyday experiences at the centre of research is discussed in this paper. The strengths and challenges of using participatory visual methods as a way of eliciting the thoughts, feelings and identities of young people within various education and training contexts in England are presented through the reflection of two ethnographies' that encouraged the use of participatory visual techniques to facilitate the gathering of data. Participatory visual approaches capture meaningful child-centred and child-generated perspectives of their everyday lives in situ [Oh, Su-Ann. 2012. 'Photofriend: Creating Visual Ethnography with Refugee Children.' Area . 44(3): 382–288. doi:10.1111/j.1475-4762.2012.01111 ]. The participatory visual method is a powerful instrument within the plethora of methods available to the ethnographer. By offering reflexive accounts of doing ethnography in an unobtrusive and child respectful way the power of ethnography is revealed via its versatility.